2019
DOI: 10.1002/cam4.2120
|View full text |Cite
|
Sign up to set email alerts
|

Tumor mutation burden and recurrent tumors in hereditary lung cancer

Abstract: Lung cancer is the leading cause of cancer death worldwide and cancer relapse accounts for the majority of cancer mortality. The mechanism is still unknown, especially in hereditary lung cancer without known actionable mutations. To identify genetic alternations involved in hereditary lung cancer and relapse is urgently needed. We collected genetic materials from a unique hereditary lung cancer patient's blood, first cancer tissue (T1), adjacent normal tissue (N1), relapse cancer tissue (T2), and adjacent norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…After stratification of LUSC patients by smoking status, we observed no significant correlation between RAD18 expression or RAD18 CNV and mutational patterns in a tri-nucleotide setting (Figure 6H ; Supplementary Figures S5I, J and 6H ). We also confirmed previous indications that both LUAD and LUSC have prominent C→ A SNVs that are less abundant in non-smokers than smokers ( 53 ).…”
Section: Resultssupporting
confidence: 91%
“…After stratification of LUSC patients by smoking status, we observed no significant correlation between RAD18 expression or RAD18 CNV and mutational patterns in a tri-nucleotide setting (Figure 6H ; Supplementary Figures S5I, J and 6H ). We also confirmed previous indications that both LUAD and LUSC have prominent C→ A SNVs that are less abundant in non-smokers than smokers ( 53 ).…”
Section: Resultssupporting
confidence: 91%
“…In specific cancer types and ethnic groups, the number of driver mutations is significantly positively correlated with cancer incidence rates ( 16 ). One lung cancer research identified that specific mutations could result in tumorigenesis or recurrence, and patients with a high burden of tumor-specific gene mutations had poor recurrence-free survival (RFS) ( 17 ). Another study showed that further validation and research on the elevated TMB and the potential impact of tumor-initiating mutations in clinically unfavorable prostate cancer could improve the outcomes of patients ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The tumorigenesis of colon adenocarcinoma is commonly known as a multi-stage process, which involves a series of genetic changes interacting with the tumor microenvironment (TME) [14,15]. This study was conducted to analyze mutations in COAD samples from the TCGA dataset and ICGC dataset.…”
Section: Discussionmentioning
confidence: 99%